2021
DOI: 10.1002/lio2.656
|View full text |Cite
|
Sign up to set email alerts
|

Tumor detection with transoral use of flexible endoscopy for unknown primary head and neck cancer

Abstract: Objectives: With the advent of new optical technologies, early pharyngolaryngeal cancerous lesions can be better visualized. Although the conventional transnasal approach offers great views of the hypopharynx and larynx, the visualization of the oropharynx and palatine tonsils is limited. Through the transoral insertion of a flexible video-laryngoscope, direct views of the oropharynx and oral cavity can be obtained.Thus, transoral examination may contribute to primary detection of cancers of unknown primary (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…While clinical practice guidelines recommend physical examination with visual endoscopic evaluation in evaluating patients at risk for HNC, 42 clinical evaluation provides incomplete oropharyngeal visualization and imperfect detection of small or submucosal tumors. [42][43][44] Furthermore, there have been few advancements in clinical examination over time, with narrow-band imaging (NBI) being the only recent innovation. [45][46][47] However, PET/CT scans have repeatedly been demonstrated to detect tumor recurrences, metastases, and second primary cancers earlier than clinical surveillance can, and can even detect tumors missed on clinical examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While clinical practice guidelines recommend physical examination with visual endoscopic evaluation in evaluating patients at risk for HNC, 42 clinical evaluation provides incomplete oropharyngeal visualization and imperfect detection of small or submucosal tumors. [42][43][44] Furthermore, there have been few advancements in clinical examination over time, with narrow-band imaging (NBI) being the only recent innovation. [45][46][47] However, PET/CT scans have repeatedly been demonstrated to detect tumor recurrences, metastases, and second primary cancers earlier than clinical surveillance can, and can even detect tumors missed on clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…While our baseline estimate of clinical surveillance sensitivity was 44%, we found that clinical sensitivity must increase to 51% for surveillance PET/CT scans to not be cost‐effective. While clinical practice guidelines recommend physical examination with visual endoscopic evaluation in evaluating patients at risk for HNC, 42 clinical evaluation provides incomplete oropharyngeal visualization and imperfect detection of small or submucosal tumors 42‐44 . Furthermore, there have been few advancements in clinical examination over time, with narrow‐band imaging (NBI) being the only recent innovation 45‐47 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a group in Japan described transoral flexible endoscopy in the clinic for patient with CUP. They found that patients tolerated the procedure well, and that it increased the detection of oropharyngeal primaries, and so this may be a promising additional investigation in future [8 ▪ ].…”
Section: Initial Investigationsmentioning
confidence: 99%
“…Ebisumoto et al reported a higher detection rate of oropharyngeal tumors with the combined approach, since the transnasal examination does not always provide sufficient visualization of the oropharynx. 13 …”
Section: Identification Of Primary Tumor Sitementioning
confidence: 99%